2013
DOI: 10.1002/ajmg.a.36358
|View full text |Cite
|
Sign up to set email alerts
|

A patient with the classic features of Phelan‐McDermid syndrome and a high immunoglobulin E level caused by a cryptic interstitial 0.72‐Mb deletion in the 22q13.2 region

Abstract: Phelan-McDermid syndrome, also known as the 22q13 deletion syndrome, is a chromosomal microdeletion syndrome characterized by neonatal hypotonia, normal growth, profound developmental delay, absent or delayed speech, and minor dysmorphic features. Almost all of the 22q13 deletions published so far have been described as terminal. It is believed that the SHANK3 gene is the major candidate gene for the neurologic features of the syndrome. Here we describe a patient with a 0.72-Mb interstitial 22q13.2 deletion, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 22 publications
3
24
0
1
Order By: Relevance
“…In addition, two patients presenting with classic clinical features of PMS have been reported to have interstitial microdeletions in the 22q13.2 region that map proximal to the SHANK3 gene and the 950 kb minimally deleted region at 22q13.31 (Figure b) (Simenson, Õiglane‐Shlik, Teek, Kuuse, & Õunap, ; Thümmler et al, ). These deletions, located solely in the 22q13.2 region, span approximately 720 and 540 kb and encompass 15 and 14 OMIM genes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, two patients presenting with classic clinical features of PMS have been reported to have interstitial microdeletions in the 22q13.2 region that map proximal to the SHANK3 gene and the 950 kb minimally deleted region at 22q13.31 (Figure b) (Simenson, Õiglane‐Shlik, Teek, Kuuse, & Õunap, ; Thümmler et al, ). These deletions, located solely in the 22q13.2 region, span approximately 720 and 540 kb and encompass 15 and 14 OMIM genes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all of the 22q13 deletions published have been described as terminal [15,30,16,12,14,20]. However, there are several cases identified in the literature that have been described as 22q13 interstitial deletion and that presented a phenotype similar to the 22q13 terminal deletion syndrome [27,24,8,29]. These observations suggest that the etiology for the neurological features must also be due to genes located proximal to SHANK3.…”
Section: Discussionmentioning
confidence: 99%
“…Generalized tonic-clonic, myoclonic, absence, and focal seizures may occur in patients with 22q13.3 deletion syndrome. [2,[4][5][6][7][8]. Soorya et al reported that 13 of 32 (41%) patients with 22q13.3 deletion syndrome had clinical seizures, including seven (22%) with febrile seizures only, four (13%) with non-febrile seizures, and two (6%) with both febrile and non-febrile seizures [9].…”
Section: Discussionmentioning
confidence: 99%